2019
DOI: 10.1016/j.ajhg.2019.02.021
|View full text |Cite
|
Sign up to set email alerts
|

The Discovery of a LEMD2-Associated Nuclear Envelopathy with Early Progeroid Appearance Suggests Advanced Applications for AI-Driven Facial Phenotyping

Abstract: Over a relatively short period of time, the clinical geneticist's ''toolbox'' has been expanded by machine-learning algorithms for image analysis, which can be applied to the task of syndrome identification on the basis of facial photographs, but these technologies harbor potential beyond the recognition of established phenotypes. Here, we comprehensively characterized two individuals with a hitherto unknown genetic disorder caused by the same de novo mutation in LEMD2 (c.1436C>T;p.Ser479Phe), the gene which e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 27 publications
1
62
0
Order By: Relevance
“…4g), which according to the previous data likely resemble cytoplasmic channels traversing the nucleus (Fichtman et al 2019). Such nuclear channels were not observed in control cell lines, and we have not observed them before either in primary cell lines of unaffected or in individuals affected by various progeroid features (Hisama et al 2011;Lessel et al 2014bLessel et al , 2017bMarbach et al 2019).…”
Section: Nuclear Abnormalities In Patient's Dermal Fibroblastssupporting
confidence: 67%
See 2 more Smart Citations
“…4g), which according to the previous data likely resemble cytoplasmic channels traversing the nucleus (Fichtman et al 2019). Such nuclear channels were not observed in control cell lines, and we have not observed them before either in primary cell lines of unaffected or in individuals affected by various progeroid features (Hisama et al 2011;Lessel et al 2014bLessel et al , 2017bMarbach et al 2019).…”
Section: Nuclear Abnormalities In Patient's Dermal Fibroblastssupporting
confidence: 67%
“…Segmental progeroid syndromes, defined as syndromes with signs of premature aging affecting more than one tissue or organ (Martin 1978), are highly heterogenous genetic disorders. Studies utilizing next-generation sequencing (NGS) approaches have revealed several novel progeroid genes in recent years (Ehmke et al 2017;Jay et al 2016;Lessel et al 2014bLessel et al , 2017bLessel et al , 2018Marbach et al 2019;Paolacci et al 2018;Puente et al 2011;Schrauwen et al 2015;Wambach et al 2018), and broadened the spectrum of phenotypes of many known progeroid conditions and the number of associated genetic causes (Lessel et al 2014a(Lessel et al , 2015Rodriguez-Garcia et al 2018;Soria-Valles et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the further course of the disease, patients often develop bilateral cataract, type 2 diabetes, skin ulcers (typically around the ankle), osteoporosis (especially of the long bones), calcification in the Achilles tendon, hypogonadism, atherosclerosis of the coronary arteries with increased risk of myocardial infarction, as well as cancers, such as soft-tissue sarcoma, osteosarcoma, melanoma, and thyroid cancer, which are rather rare in the general population (Table). The most common causes of death are cardiovascular disease and cancer; the average life expectancy is 54 years (17,18 (4,25,(36)(37)(38). Likewise, besides the two infantile SPS discussed here, there are numerous other syndromes with childhood onset, which could not be described in detail, again for lack of space.…”
Section: Juvenile/adult Segmental Progeroid Syndromesmentioning
confidence: 89%
“…Several studies have employed DeepGestalt to diagnose rare syndromes with a moderate [46] to high degree of success, namely, Cornelia de Lange syndrome (ORPHA: 199) [47], Emanuel syndrome (ORPHA:96170), and Pallister-Killian syndrome (ORPHA: 884) [48]. Besides diagnosis, DeepGestalt can also be applied to discover new RDs [49].…”
Section: Imaging-based Ddssmentioning
confidence: 99%